PERBEDAAN PERENDAMAN PLAT RESIN AKRILIK PADA TABLET PEMBERSIH GIGI TIRUAN EFFERVESCENT DAN AIR REBUSAN DAUN SIRIH TERHADAP PENURUNAN JUMLAH KOLONI JAMUR CANDIDA ALBICANS - Roza Restu Pambudi; Ratna Sulistyorini; Lisa Oktaviana Mayasari (Universitas Muhammadiyah Semarang, 2017)
Background: Denture plaque is an important factor that can caus e palatal mucos a inflammation and denture s tomatitis . Acrylic res in denture and oral cavity hygiene can be maintained from Candida albicans contamination by immers ing denture in denture cleans er at night. Denture cleans er can be made from chemical material, s uch as denture cleans er tablet effervescent and traditional material s uch as betel leafboiled water. Objective : The aim of this s tudy is to inves tigate the difference between acrylic res in plate immers ion in denture cleaner tablet effervescent and betel leaf boiled water concerning the decreas e ofCandidaalbican samount. Methodes : This is an experimental laboratory res earch. 24 acrylic res in plates are divided into 3 groups : group 1, acrylic res in immers ed in aquades for 6 hours , group 2, acrylic res in is immers ed in betel leaf boiled water for 6 hours , and grou p 3, acrylicres in is immers ed in denture cleans er tableteffervescent in 15 minutes. Result: Statis tical analys is with ANOVA tes t which is then continued with post -hoc test s hows the s ignificant difference between betel leaf boiled water and denture cleans er tablet effervescent (p<0.05). Conclus ion : It can be concluded from this s tudy that there is a lot betel leaf boiled water concerning the decrease of Candida albicans fungal colony of the denturecleanser tablet effervescent. Keywords: Candida albicans, betel leaf boiled water, denture cleanser tablet effervescent.